Common Bacterial Blight of Snap Bean in Florida - Shouan Zhang; Aaron J. Palmateer; Ken Pernezny; Jeffrey B. Jones (EDIS)
Revised! PP-62, a 3-page illustrated fact sheet by Shouan Zhang, Aaron J. Palmateer, Ken Pernezny, and Jeffrey B. Jones, describes this most frequently encountered bacterial disease of snap bean in Florida, its symptoms, cause and disease cycle, and control. Published by the UF Department of Plant Pathology, February 2009.